Reversing multidrug resistance in breast cancer cells by silencing ABC transporter genes with nanoparticle-facilitated delivery of target siRNAs - Ezharul Hoque Chowdhury; Xiang Li; Yeh‐Shiu Chu; Kunnath (2012)
Methods and results: We report that carbonate apatite-mediated delivery of the siRNAs targeting ABCG2 and ABCB1 gene transcripts in human breast cancer cells which constitutively express both of the transporter genes dose-dependently enhanced chemosensitivity to doxorubicin, paclitaxel and cisplatin, the traditionally used chemotherapeutic agents. Moreover, codelivery of two specific siRNAs targeting ABCB1 and ABCG2 transcripts resulted in a more robust increase of chemosensitivity in the cancer cells, indicating the reversal of ABC transporter-mediated multidrug resistance. Conclusion: The delivery concept of multiple siRNAs against ABC transporter genes is highly promising for preclinical and clinical investigation in reversing the multidrug resistance phenotype of breast cancer. Keywords: carbonate apatite, siRNA, gene expression, transfection, breast cancer, ABC transporter, multidrug resistance, chemosensitivity